2020
DOI: 10.1186/s12865-020-00371-y
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous immunoglobulin in primary immunodeficiency – impact of training and infusion characteristics on patient-reported outcomes

Abstract: Background: Subcutaneous immunoglobulin (SCIG) is increasingly utilized in primary immunodeficiency (PI). Understanding factors associated with treatment experience and satisfaction can optimize patient outcomes. We analyzed Immune Deficiency Foundation (IDF) survey data to evaluate patient-reported outcomes (PROs) in relation to SCIG training and infusion characteristics. Respondents' PRO scores were rank ordered into 'best', 'intermediate', and 'worst' tertiles. Predicted probabilities of being in the best t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 30 publications
(55 reference statements)
4
17
0
Order By: Relevance
“…In this study, respondents receiving SCIg reported significantly quicker infusion preparation time, actual infusion time, and post-infusion clean up time per infusion compared with IVIg users. Although SCIg infusions are typically more frequent than IVIg infusions, and total infusion time involvement over a monthly period may be the same, a recent study demonstrated that shorter infusion times per infusion were associated with substantially enhanced treatment satisfaction [ 30 ]. Given the apparent value placed by patients on shorter, flexible infusions, further infusion optimization could potentially help patients achieve more flexibility, reduce the time spent on their infusion schedule, and reduce the treatment burden of infusion regimens [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, respondents receiving SCIg reported significantly quicker infusion preparation time, actual infusion time, and post-infusion clean up time per infusion compared with IVIg users. Although SCIg infusions are typically more frequent than IVIg infusions, and total infusion time involvement over a monthly period may be the same, a recent study demonstrated that shorter infusion times per infusion were associated with substantially enhanced treatment satisfaction [ 30 ]. Given the apparent value placed by patients on shorter, flexible infusions, further infusion optimization could potentially help patients achieve more flexibility, reduce the time spent on their infusion schedule, and reduce the treatment burden of infusion regimens [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same was less true of those that had transitioned to SCIg from IVIg, and this may in part be due to them having encountered more barriers to transition to self-infusion (such as dose adjustments) or still being in the process of adjusting to the transition. Better treatment satisfaction among the SCIg naïve cohort was particularly remarkable considering their relatively short IgRT experience, since evidence suggests that treatment satisfaction is better among those with longer IgRT experience [ 30 ]. Accordingly, an alternative explanation for our finding could be that in the authors experience, many patients with immunodeficiencies start IgRT directly on SCIg in Canada, except those whose conditions are very unstable or have multifactorial obstacles (but are usually later switched to SCIg once stabilized).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite clinical benefits of IVIG or SCIG therapies, the need for repetitive infusion treatments, eventually in the setting of clinical visits can negatively impact the quality of life (QoL) of patients [71][72][73]. For patients who successfully manage home-based administration of SCIG, Administrated subcutaneously [70] Treatment location Hospital, doctor office, or infusion center [70] Home treatment by a health care professional [79] Home self-treatment [70] Administration Requires a health care professional [82] Administered by patient or caregiver after instruction by a health care professional [ More flexibility and independency [72,74] Costs More expensive than SCIG at high doses and if therapy is given over a long period of time [81,82,85,88,89] Potential to be more cost-effective in certain markets than IVIG for long-term therapy [81,82,85,88,89] the gain of flexibility and autonomy might add value and increase their QoL [71,[74][75][76]. In a conjoint survey including 252 adult patients and 66 parents of children with PID, both groups preferred a home setting, monthly frequency, fewer needle sticks, and shorter treatment durations of IG treatment relative to alternative choices (p < 0.05) [77].…”
Section: Patient Preference and Quality Of Lifementioning
confidence: 99%
“…Of note, the self-administration or administration of SCIG by a caregiver requires training by health care professionals, a high degree of independence, and high compliance to the treatment schedule [70,72]. Poor parental supervision for younger patients, attention-deficit disorders, or low compliance in general might be exclusion criteria for the SCIG treatment option.…”
Section: Patient Preference and Quality Of Lifementioning
confidence: 99%